Dyplomacja papieska wobec konfliktów na Bliskim Wschodzie – osobisty wkład Jana Pawła II w dzieło pokoju - Rudnicki, Zbigniew (Polski Przegląd Stosunków Międzynarodowych, 2018)
Papal Diplomacy in the face of conflicts in the Middle East – a personal contribution of John Paul II The traditional diplomacy of peace is characteristic for the Holy See, which for centuries has been sending envoys wherever a threat of military conflict was present. Many times in the history, the Holy See offered and undertook mediatory missions in disputes between states. Many times, Popes were personally engaged in the work of preserving peace but this engagement has never had such a special character as in the recent times. The activity of the Holy See in the field of international relations continuous to grow, embracing not only European issues but more and more global ones. The activities of predecessors of John Paul II, to mention only John XXIII and Paul VI, are clear examples. Never before has the Pope's personal engagement was so great as in the case of diplomatic efforts of John Paul II. This study presents the most important diplomatic activities of John Paul II undertaken in order to save and maintain peace. The presented cases relate to events taking place in the Middle East region, considered as one of the most unstable area in which the long-standing and awaiting solution conflicts, make it a proverbial powder keg threatening to burst at any moment. The article discusses the activities undertaken by the Holy See under the papacy of John Paul II with regard to the Israeli-Palestinian conflict, ended with military intervention of the United States the Iraqi conflict and leading to civil war the Lebanon conflict.